Labuan: its legal history and land tenure system - Mobarak Ali, Bashiran Begum; Mohamad, Nor Asiah (Malaysian Branch of the Royal Asiatic Society (MBRAS), 2009)
A prominent researcher on the history of Malaysian land tenure, Judith Sihombing, argues in line with J. R. Innes that the land registration system was first introduced in labuan by virtue of the labuan Registration of Titles to land Ordinance No.7 of 1849 and not in Selangor under the Selangor Registration of Titles Regulation No. IV of 1891. which was introduced by W. E. Maxwell. Unfortunately, neither Innes nor Sihombing investigated this matter any further. Moreover, the labuan Registration of Titles to land Ordinance No. 7 of 1849 was issued prior to the Torrens System introduced in Australia by Sir Robert Torrens (Real Property Act 1858). The question is whether the labuan Registration of Titles to land Ordinance No.7 of 1849 was a registration of land titles or a registration of deeds, or a registration of instrument of transfer. This study attempts to investigate and analyse these issues. In order to confirm that land registration was first introduced in labuan, it is necessary to study labuan legal history.